2006
DOI: 10.1080/00071660600753615
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle fibre growth and growth associated myopathy in the domestic chicken (Gallus domesticus)

Abstract: 1. Genetic selection of broilers may have pushed muscle fibres to their maximum functional size constraints. Broiler (B), female great-grandparent (GGP) and layer (L) lines were weighed, blood sampled and killed from 5 to 25 weeks of age. 2. At 25 weeks, Pectoralis major (Pm) fibre size reached by the B (65.9 microm) and GGP (59.8 microm) were 1.5 times greater than the L (38.1 microm). In the B and GGP lines, fibre growth of the Pm markedly exceeded that of the Biceps femoris (Bf) muscle. However, in the L li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 16 publications
3
53
0
7
Order By: Relevance
“…In addition to the increase in enzyme activities, those authors reported microscopic lesions, such as necrosis and basophilia, in the pectoris major and biceps muscles of 5-weekold broilers with myopathies. However, in the present study, except for the ALD, no other muscles were macroscopically or microscopically evaluated, and therefore, no comparisons with the study of MacRae et al (2006) can be made. …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition to the increase in enzyme activities, those authors reported microscopic lesions, such as necrosis and basophilia, in the pectoris major and biceps muscles of 5-weekold broilers with myopathies. However, in the present study, except for the ALD, no other muscles were macroscopically or microscopically evaluated, and therefore, no comparisons with the study of MacRae et al (2006) can be made. …”
Section: Resultsmentioning
confidence: 81%
“…Zimermann (2008) observed histologic lesions, such as degeneration, necrosis, and lympho-histiocytic infiltrate, in normal anterior latissimus dorsi muscle and in other grossly normal muscle groups of broilers; however, the authors did not analyze CK and AST levels. MacRae et al (2006) reported levels of 955 IU/L for CK and 35.1 IU/L for AST in broilers with skeletal muscle fiber growth and growth associated myopathies. In addition to the increase in enzyme activities, those authors reported microscopic lesions, such as necrosis and basophilia, in the pectoris major and biceps muscles of 5-weekold broilers with myopathies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the phenotypic differences between the two chicken breeds arise as early as the first few days of embryonic development (Clum et al, 1995;Burggren et al, 2004;Boerjan, 2004), potentially setting the stage for the breed-specific differences observed in latestage embryonic (Sato et al, 2006;Everaert et al, 2008), juvenile (Martinez-Lemus et al, 1999;Latimer and Brisbin, 1987;Odom et al, 2004) and adult (Martinez-Lemus et al, 1998;Koenen et al, 2002;Schreurs et al, 1995;McRae et al, 2006) phenotypes. Broiler embryos have faster overall development rates than layer embryos, which is first evident at 48h of development (Boerjan, 2004;Everaert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These pathologies are attributable to alterations in intracellular calcium homeostasis (Sandercock and Mitchell 2003;Sandercock et al, 2006) and consequent changes in sarcolemmal integrity and may result from excessive myofibre hypertrophy and inadequate development of support tissues and vascular supply (MacRae et al, 2006(MacRae et al, , 2007. These myopathies may have, in turn, a range of implications for both product quality and bird welfare (Mitchell, 1999).…”
Section: Fitness For Transportmentioning
confidence: 99%
“…The genetic selection of broiler chickens for improved production traits has resulted in both growthassociated and stress-induced muscle pathologies or myopathies (MacRae et al, 2006;Sandercock and Mitchell, 2003;Sandercock et al, 2006;, which are coupled to an impaired thermoregulatory capacity and consequent susceptibility to thermal stress in transport. These are important factors, since the risk of hyperthermia in commercial lines of birds is increased compared to their genetic predecessors and thus the induction of pathology and distress may be greater in the current broiler strains.…”
Section: Muscle Pathology In Broiler Chickens -Effects Of Transportmentioning
confidence: 99%